The Influence of Work Culture and Discipline on the Performance of State Civil Apparatus at the Pasar Minggu District Office, South Jakarta Administrative City - Suhaeli, Eli; Madiistriyatno, Harries; Sahim, Aswin Naldi (Jurnal Ekonomi, 2024)
The aim of the research in writing this thesis is to determine and analyze the influence of work culture on the performance of the State Civil Apparatus, to determine and analyze the influence of discipline on the Performance of the State Civil Apparatus and to determine and analyze the influence of work culture and discipline together on the Performance of the State Civil Apparatus. . This research is analytical observational research, namely the researcher makes direct observations of respondents by distributing questionnaires for analysis using quantitative research methods. Regarding research, the author used a saturated sampling technique. In this research, the author narrowed the population to 50 employees at the Pasar Minggu District Office, South Jakarta. There is an influence of Work Culture (X1) on Employee Performance (Y), because the t value for variable X1 (Work Culture) is 7.913, while the t table value for N = 70 is 1.994. So 7.913 > 1.994, it can be concluded that partially the Work Culture variable (X1) has an effect on Employee Performance (Y). There is an influence of Discipline (X2) on Employee Performance (Y), because the t value for variable X2 (Discipline) is 10.755, while the t table value for N = 70 is 1.994. So 10.755 > 1.994. It can be concluded that partially the Discipline variable (X2) has an effect on Employee Performance (Y). There is an influence of Work Culture (X1) and Discipline (X2) together on Employee Performance (Y), it is proven that the Fcount value is 302.318, while the Ftable ( 0.05) for n = 70 is 2.74. So Fcount > from Ftable ( 0.05) or 302.318 > 2.74 with a significant level of 0.000 because 0.000 < 0.05, then it can be said that Work Culture (X1) and Discipline (X2) together or simultaneously have a positive effect on Performance of employees at the Pasar Minggu District Office, South Jakarta (Y) with an R Square value of 0.900. This shows that 90% of Work Culture (X1) and Discipline (X2) together influence the performance of employees at the Pasar Minggu District Office, South Jakarta (Y), while the remaining 10% is influenced by other factors not examined in this research.